Effect of symbiotic fungi-Armillaria gallica on the yield of Gastrodia elata Bl. and insight into the response of soil microbial community - Wang, Yanhong; Xu, Jiao; Yuan, Qingsong; Guo, Lanping; Xiao, Chenghong; Yang, Changgui; Li, Liangyuan; Jiang, Weike; Zhou, Tao (Frontiers in Microbiology, 2023)
Armillaria members play important roles in the nutrient supply and growth modulation of Gastrodia elata Bl., they will undergo a severe competition with native soil organisms before colonization and symbiotic with G. elata. Unraveling the response of soil microbial organisms to symbiotic fungi will open-up new avenues to illustrate the biological mechanisms driving G. elata benefit from Armillaria. For this purpose, Armillaria strains from four main G. elata production areas in China were collected, identified, and co-planted with G. elata in Guizhou province. The result of phylogenetic tree indicated that the four Armillaria strains shared the shortest clade with Armillaria gallica. The yields of G. elata were compared to uncover the potential role of these A. gallica strains. Soil microbial DNA was extracted and sequenced using Illumina sequencing of 16S and ITS rRNA gene amplicons to decipher the changes of soil bacterial and fungal community arising from A. gallica strains. The yield of G. elata symbiosis with YN strain (A. gallica collected from Yunnan) was 4 times higher than that symbiosis with GZ strain (A. gallica collected from Guizhou) and nearly 2 times higher than that symbiosis with AH, and SX strains (A. gallica collected from Shanxi and Anhui). We found that GZ strain induced changes in bacterial, while YN strain mainly caused changes in fungal community. Similar patterns were identified in Non-Metric Multi-Dimensional Scaling (NMDS) analysis, in which GZ strain greatly separated from others in bacterial structure, while YN strain caused significant separation from other strains in fungal structure. This current work revealed the assembly and response of soil microbial community to A. gallica strains, and suggested that exotic strains of A. gallica might be helpful in improving the yield of G. elata by inducing changes in soil fungal community.